(untitled) (International Journal of Engineering and Computer Science, 2015)
: India is the second populous country in the world. India’s population is about 1.1 billion with an overall density of 336 people per square kilometer. Indian public transport supports various mode of transport such as transport by land, water, air. More than 30% of Indian population is car owners. Traffic is mainly high during peak hours within the cities [2]. In order to reduce traffic congestion, a real time ridesharing is proposed. This method is implemented by developing an android application which is user friendly and has high mobility. Real-time ridesharing is an extension of carpooling to best suite one’s preferences using the data collected from social networking. It enables users especially colleagues, classmates, to share their vehicles for travelling to the same destination or nearby destination. In addition to ridesharing, the system gives real time navigation guidance in a map. Users can set their travel to be private or make it available to some of their friends using privacy settings. The concept facilitates to include taxis or rickshaws and also other public transport systems which can set their visibility to public. In case of public transport, passengers can request to board a particular vehicle by looking up the available services in the admin processes and the requests from various users, notifies to them the nearest stopping. Implementation requires integration from social networking sites, location identified using GPS, intelligent processing of the data collected and history maintenance. For ease of use this is incorporated in mobile phones which make use of collection of social networking information and GPS data. This system supports the use of mass public transport system and travelling together which in future may become mandatory to control the depletion of fuel, make the environment green and to control traffic.